Biomolecular l-tryptophan as a hole mediator anchored on g-C3N4 exhibits remarkably enhanced photocatalytic H2 evolution. Issue 14 (15th June 2021) - Zhao, Tan; Cheang, Tuck-Yun; Chong, Han-Bao; Ling, Cong; Lu, Xiao-Jie; Li, Chen-Chuang; Fang, Xiao-Xiang; Ma, Liu-Bo; Wang, Gang; Xu, An-Wu
Abstract : A novel g-C3 N4 -based composite coupled with levorotatory-tryptophan restrains the recombination of photogenerated holes and electrons, exhibiting enhanced photocatalytic H2 production. Abstract : Photocatalytic water splitting is a promising approach to solar-to-fuel conversion. In recent years, graphitic carbon nitride (g-C3 N4 ) has triggered worldwide interest due to its eco-friendliness, low cost, and visible-light activity as a semiconductor polymer photocatalyst. However, rapid recombination of photoinduced charge carriers and low efficiency are key issues hindering the practical application of g-C3 N4 in the efficient photocatalytic hydrogen (H2 ) production field. Herein, we fabricate a novel g-C3 N4 -based composite coupled with levorotatory-tryptophan (denoted as CN/l -trp) through π–π interactions and hydrogen bonds to improve the photocatalytic performance. The redox amino acid l -trp small biomolecules act as a hole relay and thus accelerate the transfer process of holes from g-C3 N4 to triethanolamine (TEOA), which leads to more electrons shuttled to a Pt cocatalyst, and finally boosts the visible-light photocatalytic H2 evolution reaction (HER). When introducing 10 wt% l -trp, the photocatalytic H2 production rate of g-C3 N4 /10 wt% l -trp (CN/10 wt% l -trp) loaded with 1.0 wt% Pt cocatalyst composite is prominently enhanced up to 1046.0 μmol h −1 g −1, which is four times that of g-C3 N4 loaded with 1.0 wt% Pt cocatalyst (260.2 μmol h −1 g −1 ). Our study provides a novel strategy to develop an efficient, green and stable g-C3 N4 -based hybrid photocatalyst for potential application in solar-to-hydrogen energy conversion.